Conformation of cytoplasmic segments of acetylcholine receptor alpha- and beta-subunits probed by monoclonal antibodies: sensitivity of the antibody competition approach. - Kordossi, A A (1987)
The conformation of the cytoplasmic side of Torpedo marmorata acetylcholine receptor (AChR) was investigated by 22 monoclonal antibodies (mAbs) binding to known sites on the amino acid sequences 339-378 and 336-469 of the AChR alpha- and beta-subunits respectively. Competitions among these mAbs for binding on the intact AChR were compared with their competition for binding on the SDS-denatured subunits and with their corresponding epitopes previously determined on the primary structure of the subunits. We found the following: The three approaches correlated very well suggesting that these mAbs bind on the intact AChR at the same sequences determined by synthetic peptides and not on irrelevant discontinuous epitopes; this finding supports conclusions of Ratnam et al. (1986a) that the amphipathic helix M5 is exposed on the cytoplasmic side of the AChR. The subunit segments alpha 339-378 and beta 336-469 seem to be extended over large distances on the cytoplasmic surface of the AChR. The cytoplasmic surface of beta-subunit has a very immunogenic region. The mAb-competition technique is very sensitive since mAbs to epitopes separated by only about seven residues did not exclude each other, and mAbs to overlapping epitopes exhibited differential competitions with other mAbs.